Analisis Penggunaan Metode Pembelajaran Kitab Kuning di Madrasah Aliyah Tahfizhil - Nurul Izzah (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to find out how the process of learning the yellow book in Madrasah Aliyah Tahfidzul Quran Medan and in this study the analytical techniques carried out were by collecting observation data, interviews, and documentation. It turned out that at Madrasah Aliyah Tahfidzul Qur'an based on the data obtained by the school's researchers applied several methods in teaching the yellow book learning, namely being guided by practical and systematic guidebooks to recognize the basics of Nahwu science pattern 36 where this book was directly written by Tuan Guru Besar Nahwu and Shorof and taught directly by him who lives in the Madrasah Aliyah Tahfidzul Quran complex in Medan itself, conventional learning methods or in this method every educator in opening learning conveys learning knowledge orally to students in the hope of encouraging students to be more focused and teachers full control over the class. The question and answer method is carried out because the implementation of the lecture method was due to direct communication, in this method students ask the teacher or vice versa. The attack method is carried out by the educator team where all students directly face the teacher or Ustadz in turns or relay such as Simaan memorizing the Koran, the point of the amtsilati method is applied so that students can quickly understand and read the yellow book by giving a mindset to understand Arabic with the formula systematic.